Anti-icing and anti-skid composite coating and preparation method thereof
By using silicates, fluorine-containing silane organics, composite nanometal particles and other raw materials in the superhydrophobic coating, the composite coating with complex surface structures is solved, and the existing coatings have been improved in terms of anti-slip and anti-ice coating properties, and the synchronous performance and weather resistance of the coating are enhanced.
Patent Information
- Application Number
- CN202411870256.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing superhydrophobic coatings have shortcomings in improving anti-slip and anti-ice coating properties, and it is difficult to meet the anti-slip and weather resistance in special needs areas at the same time.
A composite coating is used, and its raw materials include silicates, fluorine-containing silane organics, composite nanometal particles, alkaline components and acidic components. The composite nanoparticles with complex surface structure are formed through alkali silicic acid reaction and surface modification reaction, thereby enhancing the anti-slip and anti-ice coating properties of the coating.
The anti-slip and anti-ice coating performance of the coating is achieved synchronously, which enhances the toughness and weather resistance of the coating, significantly reduces the residence time of water droplets and ice crystals on the coating surface, and effectively prevents slipping and ice coating.
Smart Images

Figure CN119613990A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coatings, and in particular to an anti-icing and anti-skid composite coating and a preparation method thereof. Background Art
[0002] A super-hydrophobic coating refers to a composite coating with a static contact angle with water droplets greater than 150 degrees and a rolling angle less than 10 degrees. It has functions such as waterproofing, self-cleaning, and anti-fouling, and therefore has a wide range of application scenarios. At present, super-hydrophobic coatings are made by modifying low surface energy components on a surface with a micro-nano rough structure or constructing roughness on a low surface energy surface to give the solid surface a super-hydrophobic function. In the case of a solid surface with a super-hydrophobic coating, based on the super-hydrophobic properties of the super-hydrophobic coating, water droplets will take away various powder particles adhering to the solid surface when sliding off the solid surface, thereby achieving a self-cleaning function.
[0003] However, most of the current superhydrophobic coatings require a relatively smooth surface to ensure that the solid surface is in the best self-cleaning performance. However, for some areas with special needs (such as hospital floors and climbing channels for high-altitude operating equipment), the coating needs to have certain anti-slip properties. In addition, in terms of power equipment, the coating is also required to have certain weather resistance, especially anti-icing performance. Summary of the invention
[0004] The present application provides an anti-icing and anti-skid composite coating and a preparation method thereof to solve the following technical problem: how to simultaneously improve the anti-skid and anti-icing properties of a superhydrophobic coating.
[0005] In a first aspect, the present application provides an anti-icing and anti-skid composite coating, wherein the raw materials of the composite coating meet the following requirements, measured by mass fraction:
[0006] Silicate: 25% to 35%, fluorine-containing silane organic matter: 5% to 15%, composite nano-metal particles: 15% to 25%, alkaline components: 0.5% to 2.5%, acidic components: 1.0% to 3.0%, and the balance is organic solvent; wherein the composite nano-metal particles include nano-iron oxide particles and nano-titanium dioxide particles, and the nano-titanium dioxide particles are used to promote the nano-iron oxide particles and the silicate to form a complex gel system under the condition of the acidic component.
[0007] Optionally, the mass fraction of the nano iron oxide particles is 10% to 15%, and the mass fraction of the nano titanium dioxide particles is 5% to 10%.
[0008] Optionally, the particle size of the nano iron oxide particles is 30 nm to 50 nm, and the particle size of the nano titanium dioxide particles is 15 nm to 25 nm.
[0009] Optionally, the silicate comprises tetrabutyl orthosilicate and / or tetraethyl orthosilicate; and / or
[0010] The fluorine-containing silane organic compound includes perfluorooctyltrichlorosilane and / or perfluorooctyltriethoxysilane; and / or
[0011] The alkaline component comprises at least one of the following: alkaline metal hydroxide, ammonia and ethylenediamine; and / or
[0012] The acidic component comprises tartaric acid and / or oxalic acid; and / or
[0013] The organic solvent includes at least one of the following: ethanol, methanol and isopropanol.
[0014] In a second aspect, the present application provides a method for preparing the composite coating according to the first aspect, the method comprising:
[0015] mixing an acidic component, nano iron oxide particles and nano titanium dioxide particles to obtain an acidic nanoparticle mixture;
[0016] Under the action of ultraviolet rays under preset lighting conditions, the acidic nanoparticle mixture, the alkaline component, the silicate and the organic solvent undergo an alkali-silicic acid reaction to obtain a coarse-grade nanoparticle dispersion;
[0017] The coarse nanoparticle dispersion is subjected to an aging treatment to obtain a nanoparticle dispersion;
[0018] The fluorine-containing silane organic matter and the nano-particle dispersion liquid are subjected to surface modification reaction to obtain a composite coating.
[0019] Optionally, the preset illumination conditions include a preset ultraviolet light wavelength and a preset illumination time; the preset ultraviolet light wavelength is 200nm to 300nm, and the preset illumination time is 15min to 25min.
[0020] Optionally, the temperature of the alkali-silicic acid reaction is 45° C. to 65° C., and the time of the alkali-silicic acid reaction is 30 min to 45 min.
[0021] Optionally, the aging treatment time is 5 to 7 days; and / or
[0022] The surface modification reaction is carried out by microwave heating, the temperature of the surface modification reaction is 40° C. to 45° C., and the time of the surface modification reaction is 2 h to 5 h.
[0023] In a third aspect, the present application provides an anti-icing and anti-slip composite coating, the raw materials of the composite coating include the composite coating described in the first aspect.
[0024] In a fourth aspect, the present application provides a method for preparing the composite coating according to the third aspect, the method comprising:
[0025] The substrate is subjected to surface treatment to obtain a rough substrate;
[0026] The composite coating described in the first aspect is coated on the surface of the rough substrate by high-pressure spraying to obtain a composite coating.
[0027] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0028] The present application provides an anti-icing and anti-skid composite coating, which uses silicate as the main raw material. Under the action of alkaline components, silicate and alkaline components undergo an alkali-silicic acid reaction to generate silicon oxide. In this process, composite nano-metal particles and acidic components are added. Based on the large specific surface area characteristics of nano-iron oxide particles and nano-titanium dioxide particles of the composite nano-metal particles, the specific surface area of silicon oxide can be effectively increased to form nano-particles with larger particle size and more uniform dispersion. In addition, under the acidic environment formed by the acidic components, the nano-titanium dioxide particles will also catalyze the production of strong oxidizing The hydroxyl radicals will participate in the alkali-silica reaction, prompting the nano-iron oxide particles and silicates to form a complex gel system in the alkaline environment formed by the alkaline components, so that composite nano-particles with a complex surface structure can be finally obtained. These composite nano-particles have a relatively rough surface, which can increase the anti-slip properties of the composite coating; in addition, these composite nano-particles are surface-modified with fluorine-containing silane organic matter to have strong hydrophobicity. Combined with nano-iron oxide particles with high thermal conductivity, ice and snow can be prevented from covering the surface of these composite nano-particles, thereby improving the anti-icing performance of the composite coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0031] Figure 1 A transmission electron microscope image of an anti-icing and anti-skid composite coating provided in Example 1 of the present application;
[0032] Figure 2A schematic flow chart of a method for preparing a composite coating provided in an embodiment of the present application;
[0033] Figure 3 A schematic diagram of a method for preparing a composite coating provided in an embodiment of the present application
[0034] Figure 4 This is a physical comparison diagram of the composite coating formed by Example 1 of the present application and Comparative Example 1 2 days after the start of the melting stage of the anti-icing experiment;
[0035] Figure 5 This is a photograph of the static contact angle between the composite coating formed by the composite coating provided in Example 1 of the present application and water. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0037] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited number (fractional or integer) within the indicated range.
[0038] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions, refers to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the mass ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the mass of substance A: the mass of substance B: the mass of substance C
[0039] =1:2:3.
[0040] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.
[0041] Figure 1 The transmission electron microscope image of an anti-icing and anti-skid composite coating provided in Example 1 of the present application is shown as an example;
[0042] like Figure 1 As shown, the embodiment of the present application provides an anti-icing and anti-skid composite coating, and the raw materials of the composite coating meet the following requirements in terms of mass fraction:
[0043] Silicate: 25% to 35%, fluorine-containing silane organic matter: 5% to 15%, composite nano-metal particles: 15% to 25%, alkaline components: 0.5% to 2.5%, acidic components: 1.0% to 3.0%, and the balance is organic solvent; wherein the composite nano-metal particles include nano-iron oxide particles and nano-titanium dioxide particles, and the nano-titanium dioxide particles are used to promote the nano-iron oxide particles and the silicate to form a complex gel system under the condition of the acidic component.
[0044] It should be noted that the mass fraction of silicate can be 25% to 35%, and the mass fraction of alkaline component can be 0.5% to 2.5%, so that the composite coating has sufficient silicate and alkaline component, and sufficient silicate can fully react with alkaline component to generate sufficient silicon oxide; in addition, the mass fraction of acidic component can be 1.0% to 3.0%, and the mass fraction of composite nano-metal particles can be 15% to 25%, so that the composite coating has sufficient acidic component and composite nano-metal particles. Under the acidic environment formed by sufficient acidic component, nano-titanium dioxide particles of composite nano-metal particles can also catalyze the generation of strong oxidizing hydroxyl radicals, so that composite nano-particles with complex surface structure can be finally obtained. These composite nano-particles have a relatively rough surface, so that the anti-slip performance of the composite coating can be increased; in addition, the mass fraction of fluorine-containing silane organic matter can be 5% to 15%, so that the composite coating has sufficient fluorine-containing silane organic matter, and sufficient fluorine-containing silane organic matter can effectively modify the surface of the formed composite nano-particles to effectively improve the hydrophobicity of the composite nano-particles.
[0045] The mass fraction of the silicate may be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%.
[0046] The mass fraction of the alkaline component may be 0.5%, 1.0%, 1.5%, 2.0% or 2.5%.
[0047] The mass fraction of the acidic component may be 1.0%, 1.5%, 2.0%, 2.5% or 3.0%.
[0048] The mass fraction of the composite nano-metal particles can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%.
[0049] The mass fraction of the fluorine-containing silane organic matter can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.
[0050] In summary, the anti-icing and anti-skid composite coating provided in the embodiment of the present application is prepared by forming a composite coating with a complex surface structure having excellent anti-skid and anti-icing properties through the synergistic effect of nano-metal particles, silicates, fluorinated silane organic matter, acidic components, alkaline components and organic solvents. This coating is not only tough and weather-resistant, but also can significantly reduce the residence time of water droplets and ice crystals on the coating surface, thereby effectively preventing slipping and icing.
[0051] In some optional embodiments, the mass fraction of the nano iron oxide particles is 10% to 15%, and the mass fraction of the nano titanium dioxide particles is 5% to 10%;
[0052] In these embodiments, the mass fraction of nano-titanium dioxide particles can be 5% to 10%, so that the composite coating has a sufficient amount of nano-titanium dioxide particles. The sufficient amount of nano-titanium dioxide particles will catalyze the production of strongly oxidizing hydroxyl radicals in the acidic environment formed by the acidic component. These hydroxyl radicals will prompt the nano-iron oxide particles and silicates to form a complex gel system in the alkaline component, so that composite nano-particles with a complex surface structure can be finally obtained to increase the anti-slip performance of the composite coating; in addition, the mass fraction of the nano-iron oxide particles can be 10% to 15%, so that the composite coating has a sufficient amount of nano-iron oxide particles. The sufficient amount of nano-iron oxide particles can form a complex gel system with silicates in the alkali-silica reaction process, so that composite nano-particles with a complex surface structure can be finally obtained; in addition, the sufficient amount of nano-iron oxide particles can improve the thermal conductivity of the composite coating to improve the anti-icing performance of the composite coating.
[0053] The mass fraction of the nano titanium dioxide particles can be 5%, 6%, 7%, 8%, 9% or 10%.
[0054] The mass fraction of the nano iron oxide particles can be 10%, 11%, 12%, 13%, 14% or 15%.
[0055] In some optional embodiments, the particle size of the nano iron oxide particles is 30nm to 50nm, and the particle size of the nano titanium dioxide particles is 15nm to 25nm;
[0056] In these embodiments, the particle size of the nano-iron oxide particles can be 30nm to 50nm, and the particle size of the nano-titanium dioxide particles can be 15nm to 25nm, so that the nano-iron oxide particles and the nano-titanium dioxide particles have sufficient specific surface area, which is beneficial to the formation of complex gel systems to form composite nanoparticles with a relatively rough surface, thereby increasing the anti-slip performance of the composite coating.
[0057] The particle size of the nano iron oxide particles can be 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.
[0058] The particle size of the nano titanium dioxide particles can be 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm or 25 nm.
[0059] In some optional embodiments, the silicate comprises tetrabutyl orthosilicate and / or tetraethyl orthosilicate; and / or
[0060] The fluorine-containing silane organic compound includes perfluorooctyltrichlorosilane and / or perfluorooctyltriethoxysilane; and / or
[0061] The alkaline component comprises at least one of the following: alkaline metal hydroxide, ammonia and ethylenediamine; and / or
[0062] The acidic component comprises tartaric acid and / or oxalic acid; and / or
[0063] The organic solvent comprises at least one of ethanol, methanol and isopropanol;
[0064] In these embodiments, the silicate may include tetrabutyl orthosilicate and / or tetraethyl orthosilicate, and the fluorine-containing silane organic matter includes perfluorooctyltrichlorosilane and / or perfluorooctyltriethoxysilane, and the alkaline component includes at least one of the following: alkaline metal hydroxide, ammonia water and ethylenediamine, and the acidic component includes tartaric acid and / or oxalic acid, and the organic solvent includes at least one of the following: ethanol, methanol and isopropanol, and a complex gel system coating with excellent anti-slip and anti-icing properties is formed through the synergistic effect of nanometal particles, silicate, fluorine-containing silane organic matter, acidic component, alkaline component and organic solvent.
[0065] It should be noted that the alkaline metal hydroxide may be sodium hydroxide or potassium hydroxide.
[0066] Figure 2 A schematic flow chart of a method for preparing a composite coating provided in an embodiment of the present application is exemplarily shown;
[0067] Based on a general inventive concept, an embodiment of the present application provides a method for preparing the composite coating, the method comprising:
[0068] S1. mixing an acidic component, nano iron oxide particles and nano titanium dioxide particles to obtain an acidic nanoparticle mixture;
[0069] S2. Under the action of ultraviolet light under preset lighting conditions, the acidic nanoparticle mixture, the alkaline component, the silicate and the organic solvent are subjected to an alkali-silicic acid reaction to obtain a coarse nanoparticle dispersion;
[0070] S3. The coarse nanoparticle dispersion is aged to obtain a nanoparticle dispersion;
[0071] S4. subjecting the fluorine-containing silane organic matter and the nanoparticle dispersion to a surface modification reaction to obtain a composite coating.
[0072] This method is a method for preparing the above-mentioned composite coating. The specific composition of the composite coating can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0073] It should be noted that, under the action of ultraviolet rays under preset lighting conditions, the acidic nanoparticle mixture, alkaline components, silicate and organic solvent are subjected to alkali-silicic acid reaction to obtain a coarse nanoparticle dispersion. This reaction is to first mix the acidic nanoparticle mixture, silicate and organic solvent for photocatalysis. The photocatalysis time is the irradiation time of ultraviolet light, and then add the alkaline component to promote the alkali-silicic acid reaction of the silicate and the acidic nanoparticle mixture, thereby obtaining composite nanoparticles with a relatively rough surface, which can increase the anti-slip performance of the composite coating.
[0074] It should be noted that the mixing speed may be 500 r / min to 1000 r / min.
[0075] In some optional embodiments, the preset illumination conditions include a preset ultraviolet light wavelength and a preset illumination time; the preset ultraviolet light wavelength is 200nm to 300nm, and the preset illumination time is 15min to 25min;
[0076] In these embodiments, the preset lighting conditions may include a preset ultraviolet light wavelength and a preset lighting time, and the preset ultraviolet light wavelength may be 200nm~300nm, and the preset lighting time may be 15min~25min, so that the ultraviolet light illumination is fully carried out, so as to promote the nano-titanium dioxide particles to catalyze the production of highly oxidizing hydroxyl radicals under the acidic environment conditions formed by the acidic components, and these hydroxyl radicals will participate in the alkali-silica reaction, promoting the nano-iron oxide particles and silicates to form a complex gel system under the alkaline environment formed by the alkaline components, so as to finally obtain composite nanoparticles with a complex surface structure. These composite nanoparticles have a relatively rough surface, which can increase the anti-slip performance of the composite coating.
[0077] The preset ultraviolet wavelength can be 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm or 300nm.
[0078] The preset illumination time may be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min.
[0079] In some optional embodiments, the temperature of the alkali-silicic acid reaction is 45°C to 65°C, and the time of the alkali-silicic acid reaction is 30min to 45min;
[0080] In these embodiments, the temperature of the alkali-silica reaction can be 45°C to 65°C, and the time of the alkali-silica reaction can be 30min to 45min, so that the alkali-silica reaction can be fully carried out, so that the nano-iron oxide particles and silicates form a complex gel system in the alkaline environment formed by the alkaline group, thereby finally obtaining composite nanoparticles with a complex surface structure. These composite nanoparticles have a relatively rough surface, which can increase the anti-slip performance of the composite coating.
[0081] The temperature of the alkali silicate reaction can be 45°C, 47°C, 49°C, 51°C, 53°C, 55°C, 57°C, 59°C, 61°C, 63°C or 65°C.
[0082] The alkali-silica reaction time can be 30 min, 33 min, 36 min, 39 min, 42 min or 45 min.
[0083] In some optional embodiments, the aging treatment time is 5 days to 7 days; and / or
[0084] The surface modification reaction is carried out by microwave heating, the temperature of the surface modification reaction is 40° C. to 45° C., and the time of the surface modification reaction is 2 h to 5 h;
[0085] In these embodiments, the aging treatment time can be 5d to 7d, which can promote the components in the coarse nanoparticle dispersion to fully react to obtain a nanoparticle dispersion with a sufficiently small particle size; in addition, the surface modification reaction is carried out by microwave heating, and the temperature of the surface modification reaction can be 40°C to 45°C, and the surface modification reaction time can be 2h to 5h, which promotes the surface modification reaction to fully proceed and effectively improve the hydrophobicity of the nanoparticle dispersion through the fluorine-containing silane organic matter.
[0086] The aging time can be 5 days, 6 days or 7 days.
[0087] The temperature of the surface modification reaction may be 40°C, 41°C, 42°C, 43°C, 44°C or 45°C.
[0088] The surface modification reaction time can be 2 h, 3 h, 4 h or 5 h.
[0089] Based on a general inventive concept, an embodiment of the present application provides an anti-icing and anti-skid composite coating, the raw materials of the composite coating include the composite coating.
[0090] The composite coating is realized based on the above-mentioned composite coating. The specific composition of the composite coating can refer to the above-mentioned embodiment. Since the composite coating adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0091] Figure 3 A schematic flow chart of a method for preparing a composite coating provided in an embodiment of the present application is exemplarily shown;
[0092] Based on a general inventive concept, such as Figure 3 As shown, the embodiment of the present application provides a method for preparing the composite coating, the method comprising:
[0093] S1. The substrate is surface treated to obtain a rough substrate;
[0094] S2. Apply the composite coating on the surface of the rough substrate by high-pressure spraying to obtain a composite coating.
[0095] This method is a method for preparing the above-mentioned composite coating. The specific composition of the composite coating can refer to the above-mentioned embodiment. Since this method adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be described one by one here.
[0096] It should be noted that the surface treatment may be a shot blasting process or a sand blasting process, so that the surface roughness of the substrate reaches 500 μm to 600 μm.
[0097] The present application is further described below in conjunction with specific examples. The experimental methods in the following examples where specific conditions are not specified are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions or conditions recommended by the manufacturer.
[0098] Example 1
[0099] like Figure 1As shown, an anti-icing and anti-skid composite coating, in terms of mass fraction, the raw materials of the composite coating meet the following requirements:
[0100] Silicate: 30%, fluorine-containing silane organic matter: 10%, composite nano-metal particles: 20%, alkaline component: 1.5%, acidic component: 2.5%, and the balance is organic solvent; wherein the composite nano-metal particles include nano-iron oxide particles and nano-titanium dioxide particles, and the nano-titanium dioxide particles are used to promote the nano-iron oxide particles and silicate to form a complex gel system under the condition of the acidic component.
[0101] The mass fraction of the nano iron oxide particles is 12%, and the mass fraction of the nano titanium dioxide particles is 8%.
[0102] The particle size of the nano iron oxide particles is 40 nm, and the particle size of the nano titanium dioxide particles is 20 nm.
[0103] The silicate comprises tetrabutyl orthosilicate and tetraethyl orthosilicate, and the mass ratio of tetrabutyl orthosilicate to tetraethyl orthosilicate is 1:1;
[0104] The fluorinated silane organic compound is perfluorooctyltrichlorosilane;
[0105] The alkaline component is: sodium hydroxide and ammonia water, and the mass ratio of the sodium hydroxide to the ammonia water is 2:1;
[0106] The acidic component is tartaric acid;
[0107] The organic solvent is ethanol.
[0108] like Figure 2 As shown, a method for preparing a composite coating comprises:
[0109] S1. mixing an acidic component, nano iron oxide particles and nano titanium dioxide particles to obtain an acidic nanoparticle mixture;
[0110] S2. Under the action of ultraviolet light under preset lighting conditions, the acidic nanoparticle mixture, the alkaline component, the silicate and the organic solvent are subjected to an alkali-silicic acid reaction to obtain a coarse nanoparticle dispersion;
[0111] S3. The coarse nanoparticle dispersion is aged to obtain a nanoparticle dispersion;
[0112] S4. Performing surface modification reaction on the fluorine-containing silane organic matter and the nanoparticle dispersion to obtain a composite coating.
[0113] The preset illumination conditions include a preset ultraviolet light wavelength and a preset illumination time; the preset ultraviolet light wavelength is 250nm, and the preset illumination time is 20min.
[0114] The temperature of the alkali-silicic acid reaction is 55° C., and the time of the alkali-silicic acid reaction is 40 minutes.
[0115] The aging time is 6 days;
[0116] The surface modification reaction was carried out by microwave heating at a temperature of 42° C. and a time of 3 h.
[0117] Example 2
[0118] Based on the contents disclosed in Example 1, the following modifications are further made:
[0119] In terms of mass fraction, the raw materials of the composite coating meet the following requirements:
[0120] Silicate ester: 25%, fluorine-containing silane organic matter: 5%, composite nano-metal particles: 15%, alkaline component: 0.5%, acidic component: 1.0%, and the balance is organic solvent.
[0121] The mass fraction of the nano iron oxide particles is 10%, and the mass fraction of the nano titanium dioxide particles is 5%.
[0122] The particle size of the nano iron oxide particles is 50 nm, and the particle size of the nano titanium dioxide particles is 25 nm.
[0123] Example 3
[0124] Based on the contents disclosed in Example 1, the following modifications are further made:
[0125] In terms of mass fraction, the raw materials of the composite coating meet the following requirements:
[0126] Silicate ester: 35%, fluorine-containing silane organic matter: 15%, composite nano-metal particles: 25%, alkaline component: 2.5%, acidic component: 3.0%, and the balance is organic solvent.
[0127] The mass fraction of the nano iron oxide particles is 15%, and the mass fraction of the nano titanium dioxide particles is 10%.
[0128] The particle size of the nano iron oxide particles is 30 nm, and the particle size of the nano titanium dioxide particles is 15 nm.
[0129] Example 4
[0130] Based on the contents disclosed in Example 1, the following modifications are further made:
[0131] The preset ultraviolet wavelength is 200nm, and the preset illumination time is 25min.
[0132] The temperature of the alkali-silicic acid reaction is 45° C., and the time of the alkali-silicic acid reaction is 45 min.
[0133] The aging time is 5 days;
[0134] The temperature of the surface modification reaction was 40°C, and the time of the surface modification reaction was 5 h.
[0135] Example 5
[0136] Based on the contents disclosed in Example 1, the following modifications are further made:
[0137] The preset ultraviolet wavelength is 300nm, and the preset illumination time is 15min.
[0138] The temperature of the alkali-silicic acid reaction is 65° C., and the time of the alkali-silicic acid reaction is 30 min.
[0139] The aging time is 7 days;
[0140] The temperature of the surface modification reaction is 45°C, and the time of the surface modification reaction is 2h.
[0141] Comparative Example 1
[0142] Based on the contents disclosed in Example 1, the following modifications are further made:
[0143] A commercially available anti-ice and anti-icing self-cleaning coating (purchased from a certain new material company) was used.
[0144] Comparative Example 2
[0145] Based on the contents disclosed in Example 1, the following modifications are further made:
[0146] No composite nano-metal particles are added.
[0147] Comparative Example 3
[0148] Based on the contents disclosed in Example 1, the following modifications are further made:
[0149] No nano iron oxide particles were added.
[0150] Comparative Example 4
[0151] Based on the contents disclosed in Example 1, the following modifications are further made:
[0152] No nano titanium dioxide particles were added.
[0153] Comparative Example 5
[0154] Based on the contents disclosed in Example 1, the following modifications are further made:
[0155] No acidic components were added.
[0156] Comparative Example 6
[0157] Based on the contents disclosed in Example 1, the following modifications are further made:
[0158] No ultraviolet light exposure.
[0159] Related experiments and effect data:
[0160] 1. The composite coating obtained in Example 1 was tested by scanning electron microscopy. The test results were as follows: Figure 1 As shown, this indicates that the composite coating has composite nanoparticles with complex surface structure.
[0161] 2. The composite coating obtained in each embodiment and comparative example is applied to the surface of the cable in the following manner:
[0162] like Figure 3 As shown, a method for preparing a composite coating, the method comprising:
[0163] S1. Surface treatment of the cable to obtain a rough cable;
[0164] S2. Apply the composite coating on the surface of the rough substrate by high-pressure spraying to obtain a composite coating.
[0165] The roughness of the composite coating was detected, and then the cable with the composite coating was subjected to an anti-icing test in an actual environment (snowy weather in a mountainous area, outdoor temperature -10℃~0℃, and snow lasting for more than 3 days). The time from the snow covering the cable to melting and leaking out of most of the surface was counted (the time when more than 80% of the area leaked out on a sunny day by telescope observation was the cutoff time). The results are shown in Table 1 and Figure 4 shown.
[0166] Table 1 Roughness and melting time results of the composite coatings of various embodiments and comparative examples
[0167]
[0168]
[0169] From Table 1 and Figure 4It can be seen that the anti-icing and anti-skid composite coating provided in the embodiment of the present application forms a composite coating with a complex surface structure having excellent anti-skid and anti-icing properties through the synergistic effect of nano-metal particles, silicates, fluorinated silane organic matter, acidic components, alkaline components and organic solvents. This coating is not only tough and weather-resistant, but also can significantly reduce the residence time of water droplets and ice crystals on the coating surface, thereby effectively preventing the occurrence of slipping and icing; in addition, it is found through actual experiments that the composite coating formed by the composite coating has a high roughness of 43.0μm to 47.0μm, and has good anti-icing properties.
[0170] In addition, it can be seen from Comparative Examples 3 and 4 that if nano-titanium dioxide is not used, the photocatalytic process will be difficult to carry out, and it will be difficult to obtain a composite coating with a complex surface structure, which will reduce the roughness of the composite coating; and if nano-iron oxide is not used, the icing time will be slightly increased, which may be determined by the thermal conductivity of nano-iron oxide.
[0171] In addition, it can be seen from Comparative Example 5 that even without adding an acidic component, the roughness is similar to that of the example. This may be because silicate itself is acidic and the amount added may just promote the photocatalytic reaction.
[0172] In addition, it can be seen from Comparative Example 6 that if ultraviolet light is not irradiated, photocatalysis is difficult to carry out under normal light, and it is difficult to obtain a composite coating with a complex surface structure, which reduces the roughness of the composite coating.
[0173] 3. Hydrophobic performance test: The coating obtained in Example 1 was prepared into a composite coating according to the above experiment, and the static contact angle between the composite coating and water was tested. The results are as follows: Figure 5 As shown, the static contact angle of the composite coating with water is greater than 155°, while subsequent results show that the dynamic angle of the composite coating with water is less than 4°, which indicates that the composite coating has good hydrophobic properties.
[0174] In summary, the embodiments of the present application provide an anti-icing and anti-skid composite coating, which forms a composite coating with a complex surface structure having excellent anti-skid and anti-icing properties through the synergistic effect of nano-metal particles, silicates, fluorinated silane organics, acidic components, alkaline components and organic solvents.
[0175] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present application, but will conform to the widest range consistent with the principles and novel features applied for by the present application.
Claims
1. An anti-icing and anti-skid composite coating, wherein the raw materials of the composite coating meet the following requirements by mass fraction: Silicate: 25% to 35%, fluorine-containing silane organic matter: 5% to 15%, composite nano-metal particles: 15% to 25%, alkaline component: 0.5% to 2.5%, acidic component: 1.0% to 3.0%, and the balance is organic solvent; wherein, The composite nano-metal particles include nano-iron oxide particles and nano-titanium dioxide particles. The nano-titanium dioxide particles are used to promote the nano-iron oxide particles and the silicate to form a complex gel system under the condition of the acidic component.
2. The composite coating according to claim 1, wherein the mass fraction of the nano iron oxide particles is 10% to 15%, and the mass fraction of the nano titanium dioxide particles is 5% to 10%.
3. The composite coating according to claim 1, wherein the particle size of the nano iron oxide particles is 30 nm to 50 nm, and the particle size of the nano titanium dioxide particles is 15 nm to 25 nm.
4. The composite coating according to claim 1, wherein the silicate comprises tetrabutyl orthosilicate and / or tetraethyl orthosilicate; and / or The fluorine-containing silane organic compound includes perfluorooctyltrichlorosilane and / or perfluorooctyltriethoxysilane; and / or The alkaline component comprises at least one of the following: alkaline metal hydroxide, ammonia and ethylenediamine; and / or The acidic component comprises tartaric acid and / or oxalic acid; and / or The organic solvent includes at least one of the following: ethanol, methanol and isopropanol.
5. A method for preparing the composite coating according to any one of claims 1 to 4, the method comprising: mixing an acidic component, nano iron oxide particles and nano titanium dioxide particles to obtain an acidic nanoparticle mixture; Under the action of ultraviolet rays under preset lighting conditions, the acidic nanoparticle mixture, the alkaline component, the silicate and the organic solvent undergo an alkali-silicic acid reaction to obtain a coarse-grade nanoparticle dispersion; The coarse nanoparticle dispersion is subjected to an aging treatment to obtain a nanoparticle dispersion; The fluorine-containing silane organic matter and the nano-particle dispersion liquid are subjected to surface modification reaction to obtain a composite coating.
6. According to the method of claim 5, the preset illumination conditions include a preset ultraviolet light wavelength and a preset illumination time; the preset ultraviolet light wavelength is 200nm to 300nm, and the preset illumination time is 15min to 25min.
7. The method according to claim 5, wherein the temperature of the alkali-silicic acid reaction is 45°C to 65°C, and the time of the alkali-silicic acid reaction is 30 min to 45 min.
8. The method according to claim 5, wherein the aging treatment time is 5 to 7 days; and / or The surface modification reaction is carried out by microwave heating, the temperature of the surface modification reaction is 40° C. to 45° C., and the time of the surface modification reaction is 2 h to 5 h.
9. An anti-icing and anti-slip composite coating, the raw material of the composite coating comprising the composite coating according to any one of claims 1 to 4.
10. A method for preparing the composite coating according to claim 9, the method comprising: The substrate is subjected to surface treatment to obtain a rough substrate; The composite coating according to any one of claims 1 to 4 is applied on the surface of the rough substrate by high-pressure spraying to obtain a composite coating.
Citation Information
Patent Citations
Method for preparing superhydrophobic anti-icing paint and coating
CN104629620A
Super-hydrophobic nanometer coating, manufacturing method and super-hydrophobic nanometer coating object
CN105440747A
Large-scale preparation method of transparent super-hydrophobic / super-amphiphobic coating
CN106800885A
Preparation method of super-hydrophobic and oleophobic coating
CN118460108A
Hydrophobic and Lyophobic Coating
US20080090004A1